Water mediated redox-neutral cleavage of arylalkenes via photoredox catalysis - Ke Liao; Yuqi Fang; Lei Sheng; Jiean Chen; Yong Huang (Nature Communications, 2024)
Abstract Cleavage of carbon-carbon bonds remains a challenging task in organic synthesis. Traditional methods for splitting Csp2=Csp2 bonds into two halves typically involve non-redox (metathesis) or oxidative (ozonolysis) mechanisms, limiting their synthetic potential. Disproportionative deconstruction of alkenes, which yields one reduced and one oxidized fragment, remains an unexplored area. In this study, we introduce a redox-neutral approach for deleting a Csp2 carbon unit from substituted arylalkenes, resulting in the formation of an arene (reduction) and a carbonyl product (oxidation). This transformation is believed to proceed through a mechanistic sequence involving visible-light-promoted anti-Markovnikov hydration, followed by photoredox cleavage of Csp3-Csp3 bond in the alcohol intermediate. A crucial consideration in this design is addressing the compatibility between the highly reactive oxy radical species in the latter step and the required hydrogen-atom-transfer (HAT) reagent for both steps. We found that ethyl thioglycolate serves as the optimal hydrogen-atom shuttle, offering remarkable chemoselectivity among multiple potential HAT events in this transformation. By using D2O, we successfully prepared dideuteromethylated (-CD2H) arenes with good heavy atom enrichment. This work presents a redox-neutral alternative for alkene deconstruction, with considerable potential in late-stage modification of complex molecules.